The "Power" Brow Lift: Efficient Correction of the Paralyzed Brow. (28th November 2013) - Hohman, Marc H.; Silver, Amanda L.; Henstrom, Douglas K.; Cheney, Mack L.; Hadlock, Tessa A.
Abstract : Purpose . To describe a novel approach to brow ptosis correction and evaluate its long-term efficacy in patients with facial-paralysis-associated brow ptosis. Methods . Twenty-two patients aged from 50 to 90 years underwent "power" brow lifting, involving 3 intrabrow stab incisions and suture suspension of the brow to the frontal calvarium via titanium miniplate. Long-term results of the operation were assessed retrospectively. Pre- and postoperative photographs were measured with FACE-gram software to evaluate efficacy of the procedure. Results . Seventeen patients who underwent "power" brow lift were available for postoperative evaluation. Among them, follow-up length ranged from 12 to 448 days. The average post-operative change in brow height was 5.7 mm, which was statistically significant (P < 0.01 ). There were no complications. Conclusions . The "power" brow procedure can help to restore upper facial symmetry and visual fields and improve periocular hygiene. The operation is easily performed in an office setting, under local anesthesia, and appears to provide reliable long-term results. The time required to perform the procedure is far less than that required for a standard direct brow lift; there is no risk of postoperative forehead hypesthesia, and there is no superciliary scar.